Experimental investigation of high-power continuous-wave fiber optical parametric amplifiers and oscillators. - Rohit Malik (2010)
Fiber optical parametric amplifiers (OPAs) are based on a highly-efficient four-wave mixing process. Their capability to give very high gain and large bandwidths have made them an attractive candidate for providing higher bandwidths for future telecommunication systems, such as wavelength-division multiplexed (WDM) photonics networks. In dynamic photonic networks a where number of channels are dropped and/or added all the time, the OPA gain for the other channels is affected. In this thesis we employed a well-known gain control technique, all-optical gain clamping (AOGC), and reduced the gain variation of fiber OPAs below 0.5 dB, under varying input conditions. We also showed an improvement in power penalties o at the bit-error rate of 10-8, from 2.5 dB to 0.5 dB for on/off keying modulation. We also investigated fiber optical parametric oscillators (OPOs). Using fiber OPAs as gain medium we realized two different continuous-wave (CW) OPOs, centred at 1561 nm and 1593 nm. One gave us watt-level output power from 1600 nm to 1670 nm, with overall tuning range of 211 nm. The output linewidth of signal and idler was measured to be 0.08 nm and 0.15 nm respectively. The OPO centred at 1593 nm gave us a record tuning range of 254 nm, and with 3 dB output coupling fraction, it gave us large output powers (20-27 dBm) from 1610 nm to 1720 nm. Using a large seed generated by a watt-level fiber OPO in the U-band, and using 3 W of CW pump source in the C-band for Raman amplification, we generated 3 W of CW output power. This gave us nearly 100% conversion efficiency. Launching a high-power CW pump with narrow linewidth into a fiber makes stimulated Brillouin scattering (SBS) a major problem. We investigated an SBS suppressor, based on a common technique of phase dithering of the pump to suppress the SBS. We compared a multitone modulation technique to modulation with a pseudo-random bit sequence (PRBS), and we showed that it can increase the SBS threshold by 4.18 dB, and is less expensive to implement.